Kepemimpinan Agile Dalam Menghadapi Tantangan VUCA di Era Digital - Anisa Nur Maulidiyah; Izzatul Masruroh; Mochammad Isa Anshori (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Agile leadership has emerged as a strategic response to the challenges faced by organizations in the digital era, particularly within a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment. The rapidly changing business landscape requires organizations to adapt quickly and make decisions with flexibility. Agile leadership offers an approach that emphasizes adaptability, collaboration, innovation, and the courage to experiment and learn from failure through the principle of "fail fast, learn fast." This approach helps teams develop solutions iteratively, test new ideas, and respond to market changes more effectively and efficiently.This article discusses the critical role of Agile leaders in supporting organizational transformation by fostering a culture of openness, distributing responsibilities more evenly, and creating an environment that promotes individual and team growth. Through case studies of several leading technology companies that have successfully implemented Agile leadership, the article illustrates how this approach can enhance business resilience, accelerate innovation processes, and provide sustainable added value for stakeholders.In conclusion, Agile leadership is not merely a new management style but a strategic necessity in facing the challenges of the digital age. By promoting cross-functional collaboration, fast decision-making, and a continuous learning orientation, Agile leaders can guide organizations to remain relevant, competitive, and adaptive in an increasingly fast-paced and complex market environment.